Ser docente universitário aposentado : memórias e narrativas de vida - Cogo, Tadia Carolina (2011)
It is analyzed in this thesis, memories and life narratives of retired professors from the Passo Fundo University. Starting from this perspective, means that human aging Consist of a complex process not yet considered in its multiple dimensions. The aim of this work is part of this discussion, especially regarding the analysis of memories and narratives about the life of this specific group of professionals who had the experience of retirement, that displaced them directly or indirectly from the world of work. So has the purpose of knowing the different ways of living with "old age" and understand how these individuals had Built their identities through memories, recollections and representations of the past and how it may be possible to explain this professional group and their narratives in the conception of collective memory by Maurice Halbwachs. In terms of methodology, qualitative research, a multidisciplinarybrand, allows us to respond to particular issues that usually can not be quantified because it encompasses the realm of subjectivity. The guiding thread of this study is based on the study of memories and narratives of life through interviews with subjects selected from objective criteria: teachers from different subject areas, which worked mainly on teaching activities, not discarding, if they had developed administrative activities, research or extension occasionally. In different life cycles, men and women, have lived in places where labor relations are decisive because since the childhood, the family, community, school and leisure, socioeconomic and cultural conditions are mediated by the idea of subsistence and social hierarchy. The disruption that accompany the time of retirement gains meanings that go beyond the distance with the world of work. For the most people it means the irreversible entry in the last cycle of life, that is, old age. For this group of teachers, retirement are seen as a watershed in the experience of individual life